Genome-wide identification and analysis of anthocyanin synthesis-related R2R3-MYB genes in Cymbidium goeringii - Chen, Jiating; Bi, Yuan-Yang; Wang, Qian-Qian; Liu, Ding-Kun; Zhang, Diyang; Ding, Xiangqing; Liu, Zhong-Jian; Chen, Shi-Pin (Frontiers in Plant Science, 2022)
The MYB gene family plays a vital regulatory role in plant metabolism, stress response, and floral color. The R2R3-MYB gene family of C. goeringii was identified, and its expression was analyzed using bioinformatics in this article. The R2R3-MYB genes of Arabidopsis thaliana were used as a reference to determine 104 CgMYB genes and categorize them into 22 subfamilies. Exon/intron organizations and conserved motif analysis revealed that the majority of CgMYB genes were highly conserved, and chromosome localization and collinearity analysis provided evidence of tandem duplication and segmental duplication events, indicating the phenomenon of gene family expansion and contraction. The function of CgMYB genes was analyzed by cis-acting element and gene ontology (GO) enrichment. In addition, we selected CgMYB91 and CgMYB32 for RT–qPCR, suggesting that CgMYB91 and CgMYB32 are associated with anthocyanin formation. In short, this study provides a comprehensive and specific function of the R2R3-MYB transcription factors (TFs) in orchids.